To simplify the expression \( \sqrt{25} \cdot \sqrt{49} \), we can use the property of square roots that states \( \sqrt{a} \cdot \sqrt{b} = \sqrt{a \cdot b} \).
First, we calculate the square roots of the individual numbers:
\[ \sqrt{25} = 5 \quad \text{and} \quad \sqrt{49} = 7 \]
Now, we can multiply these results:
\[ \sqrt{25} \cdot \sqrt{49} = 5 \cdot 7 = 35 \]
Alternatively, applying the property of square roots directly gives:
\[ \sqrt{25} \cdot \sqrt{49} = \sqrt{25 \cdot 49} \]
Calculating \( 25 \cdot 49 \):
\[ 25 \cdot 49 = 1225 \]
Now, we find \( \sqrt{1225} \).
Since \( 1225 = 35^2 \):
\[ \sqrt{1225} = 35 \]
Thus, in either approach, the final answer is:
\[ \boxed{35} \]